The grounded theory of Coalescence of Perceptions, Practice and Power: An understanding of governance in midwifery practice. (18th November 2022) - Ferguson, Bridget; Baldwin, Adele; Henderson, Amanda; Harvey, Clare
Abstract: Aims: This study aimed to understand midwifery care during labour, particularly decision‐making processes, within Australian health systems. Background: Midwifery, founded on a wellness model of motherhood, is at risk of being medicalized. Whilst medical intervention is lifesaving, it requires judicious use. Governance provides oversight to care. Exploring decision‐making contributes to understanding governance of practices. Method: Straussian grounded theory using semi‐structured interviews. Eighteen Australian registered midwives were interviewed about their practice when caring for women during labour. Results: Midwives were caught between divergent positions; birth as natural versus birth as risk. Experienced midwives discussed focussing on the woman, yet less experienced were preoccupied with mandatory protocols like early warning tools. Practice was governed by midwives approach within context of labour. The final theory: The Coalescence of Perceptions, Practice and Power, comprising three categories: perceptions and behaviour, shifting practice and power within practice, emerged. Conclusions: Coalescence Theory elucidates how professional decision making by midwives during care provision is subject to power within practice, thereby governed by tensions, competing priorities and organizational mandates. Implications for Midwifery Managers: Midwifery managers are well positioned to negotiate the nuanced space that envelopes birthing processes, namely, expert knowledge, policy mandates and staffing capability and resources, for effective collaborative governance. In this way, managers sustain good governance.